Sound of darkness - Graham, Heather (Graham, Heather. Krewe of hunters., 2022)
Women are being taken in Virginia, and FBI agent Mark Gallagher is determined to put a stop to it. Certain he's closing in on the killer known as The Embracer, Mark is less than thrilled when he's partnered with rookie agent Colleen Law, worried she's a liability when there's so much at stake. But like everyone in the Krewe of Hunters, Colleen has talents that extend beyond the usual investigative toolbox. She can hear the voices of the victims in her head, and they're telling her she and Mark are near to uncovering the truth. When Mark's prime suspect takes a liking to Colleen, he's surprisingly protective of his new partner, even as he admits her connection to the victims is key. But tense interrogations turn dangerously personal when someone close to Colleen goes missing, luring the agents deep into the shadows of wooded rural Virginia, where nobody can hear them scream.